A small dose of dezocine suppresses remifentanil-induced cough in general anesthesia induction: a prospective, randomized, controlled study - Rui Ma; Yu Wei; Zifeng Xu (BMC Anesthesiology, 2020)
Abstract Background The aim of this prospective randomized controlled study was to evaluate whether pretreatment with a small dose of dezocine could prevent remifentanil-induced cough in general anesthesia induction. Trial design a prospective, randomized, controlled study. Methods A total of 210 patients receiving elective operative hysteroscopy from December 2018 to April 2019 were enrolled in the present study. They were randomly equally separated into dezocine group (n = 105) and control group (n = 105). Patients were intravenously pre-administrated with dezocine 0.03 mg/kg (diluted to 5 mL) or the same volume of normal saline 1 min prior to remifentanil infusion. One minute later, intravenous injection of propofol 1.5 mg/kg and cisatracurium 0.1 mg/kg were given to all patients for induction of general anesthesia. The counts of coughs occurred during the anesthesia induction period were recorded and the severity of cough was scaled. Results There were 7 cases of mild cough in dezocine group and 18 cases of mild cough, 12 cases of moderate cough and 4 cases of severe cough in control group. The incidence rate of cough was significantly lower and the severity of cough was obviously relieved in dezocine group compared to control group (6.67% vs. 32.38%, P <  0.001). The two groups were not significantly different in heart rate and mean arterial pressure before the induction, before and after the intubation, and in operating time and postoperative visual analog scale pain scores. Conclusion This study recommends the efficacy and safety of a pretreatment with a small dose of dezocine in reducing remifentanil-induced cough during general anesthesia. Trial Registration ChiCTR2000032035 . Date of registration: Retrospectively registered on 2020/04/18.